IMPLEMENTATION OF THE OPEN-ENDED MODEL IN ISLAMIC RELIGIOUS EDUCATION LEARNING IN JUNIOR HIGH SCHOOL - Ramadhani, Laili; Iman, Nurul; Ramadhani, Suci; Sriwardona (Mandeh : Jurnal Pendidikan Islam, 2024)
The problem in this study is the less than optimal efforts of Islamic Religious Education teachers in implementing the open-ended learning model for seventh-grade students at Junior High School Negeri 1 Kinali, West Pasaman Regency. The impact is seen in the low level of active student participation, where most students tend to be quiet, passive, and less likely to contribute to the learning process. The purpose of this study is to describe the efforts of Islamic Religious Education teachers in implementing the open-ended model and to identify supporting and inhibiting factors in its implementation. This study uses a qualitative approach with descriptive methods to describe in detail and in depth the teachers' efforts in implementing the model. The study was also conducted from an Islamic religious education perspective, which views learning as a means of instilling values, attitudes, and critical thinking skills in students. The research subjects consisted of Islamic Religious Education teachers and seventh-grade students. Data collection techniques were carried out through interviews, observation, and documentation, then analyzed qualitatively by considering the perspectives of teachers and students. The results show that teachers' efforts include lesson planning with appropriate objectives, materials, methods, and media, implementation through the presentation of open-ended problems that encourage critical and creative thinking, and evaluation that assesses various possible answers. Supporting factors include school support, student enthusiasm, and the availability of learning media. Inhibiting factors include time constraints, differences in student abilities, and a lack of teacher training. This research can serve as baseline data for further research efforts to improve the quality of Islamic Religious Education learning.